If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2-(3x+2)=8-x-4-2x
We move all terms to the left:
2-(3x+2)-(8-x-4-2x)=0
We add all the numbers together, and all the variables
-(3x+2)-(-3x+4)+2=0
We get rid of parentheses
-3x+3x-2-4+2=0
We add all the numbers together, and all the variables
-4!=0
There is no solution for this equation
| -15d=4.5 | | 7(x+3=-49 | | -18=2+3(d+7) | | -2(2k-4)=24 | | 16−5a+2a−1=41−a | | 4x-10/5=2x+8 | | 3=1/5+x | | (5x-5)=(7x+1) | | -5-3x=56-28x | | -45=5/3+5b | | 2+3x=-2(6-2x) | | 2(3-h)6=-5h | | -2(14-6x)=20 | | x∧2=4 | | 4x+8=2x+15–x+2 | | 7=1.50x | | 0.12x=420 | | 6a+3=16 | | (x-17)(7x+5)=0 | | -24=−24=-3w+21−3w+21 | | 4x•9=37 | | 8x-1=7x-9 | | -5+n/7=-7 | | 2(n+3)+4(n+2)=74 | | 108+2x+6=13x-7 | | m^2=0.64 | | 15x=6.25x+1890 | | 8(x+4)-3=2x+6(4+x) | | -12=3k-6 | | 6p-3=8-4p | | b3-4=3 | | a+2.8=1.9 |